Persepsi UKM Terhadap Indikator People, Profit dan Planet dalam Konsep Sustainable Entrepreneurship - Syamsuri Syamsuri; Mashudi Mashudi (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2022)
Sustainable Entrepreneurship emphasizes the importance of paying attention to the environment and social in running a business without looking at profit only, so that the sustainability of the business and its natural surroundings are maintained properly. This study aims to determine the perception of SMEs on the indicators of People, Profit, and Planet in the concept of Sustainable Entrepreneurship. The approach chosen in this research is quantitative using descriptive method and is included in the type of cross-sectional study. The population is an infinite population, namely SMEs in 3 districts/cities in West Kalimantan with special considerations, with a total sample of 75 SMEs taken by incidental sampling and determined by certain criteria. Collecting data through questionnaires and analyzed quantitatively descriptively. The research findings show that SME actors consider the concept of Sustainable Entrepreneurship important to be applied in their business based on people, profit and planet indicators, where planetary indicators are seen from the workforce, community and partners; profit indicators are seen from benefits and networks; as well as planetary indicators in terms of environmental resources and technology. The implication of this research is that it can be considered by local governments in implementing sustainable entrepreneurship policies.